Design and Synthesis of Novel Phenylpiperazine Derivatives as Potential Anticonvulsant Agents. Issue 12 (12th October 2015) - Habib, Monica M. W.; Abdelfattah, Mohamed A. O.; Abadi, Ashraf H.
Abstract : Eighteen new 5‐benzylidene‐3‐(4‐arylpiperazin‐1‐ylmethyl)‐2‐thioxo‐imidazolidin‐4‐ones were designed as hybrid structures from previously reported anticonvulsant compounds, synthesized and tested for anticonvulsant activity. Initial anticonvulsant screening was performed using the strychnine (2 mg/kg IP) potent generalized‐induced seizure and pentylenetetrazole (PTZ) (60 mg/kg IP) acute clonic‐induced convulsion screens in mice. All the molecules were found to be effective in at least one seizure model, compounds10, 13, 15, 17, and18 were active against both types of seizures induced. Compound13 turned out to be the most active candidate within the strychnine model, having an average survival time of 6 min close to that of the positive control phenytoin, while compound8 showed 100% protection from the induced PTZ seizures, resembling the protection of the positive control phenobarbital. Initial SAR studies for anticonvulsant activity are discussed. Abstract : A series of new 5‐benzylidene‐3‐(4‐arylpiperazin‐1‐ylmethyl)‐2‐thioxo‐imidazolidin‐4‐ones were designed as hybrid structures from previously reported anticonvulsant compounds. All the molecules were effective in either the generalized‐induced seizure (strychnine) or the acute clonic‐induced seizure (PTZ) model. Initial structure–activity relationship results for anticonvulsant activity are discussed.